Chemistry of Polymeric Metal Chelates - Dzhardimalieva, Gulzhian I. (Springer Series in Materials Science,, 2018)
This book deals with the chemistry of polymeric metal chelates. The main results and the production and chemical structure of polymers with chelate units as well as the specificity of metal complex binding of different structure are presented here. This book also reveals the transformations which components undergo in the course of chelation. Special attention is paid not only to synthetic but also to natural (including living) systems. The usage of polymeric metal chelates and their development are exained. The related research was performed for chelates with chain structure. This book is useful to researchers being activ in synthesis and design of macromolecular metal chelates.